The effect of X-rays leaking from the X-ray device on the human body - Fatima A. Naji; Maysaa Younis Ali (Genius Journals, 2022)
That X-rays in the field of different fields is that X-rays are used in the field of printing in the field of printing. Bones and dental abnormalities are also used to detect traces and organize crystals. and that leads to an effect that leads to its effect, and that leads to leads to causes that to happen. And to get a fresher out of the body. It is not necessary to shed sexual infrared. And the danger multiplies many times when using a fluorescent plate, ie, the radioscope. Take samples from take samples from the analysis. As for the diagnosis by fluorescent plate, it takes approximately thirty 183 seconds, which is a thousand times more than the image. X-ray medical diagnosis. Many children in many dreams. Should it be avoided? On the other hand, some surgeons use a fluorescent plate in order to put a certain part of the human body in place precisely. This way of working will affect the attending physician. A reference to a reference to the rays refers to this danger to humans from the rays that send x-rays in diagnosing rays before x-rays in cases of necessity. The lecture is in the field of the United Nations work This danger does not necessarily motivate some researchers for some time to research study. The progress of science, any science, subject to the rush of those interested in it.
Keywords: X-rays; human body; electromagnetic radiation